Pelaksanaan Handover Perawat dengan Komunikasi SBAR pada Pelayanan Keperawatan - Nasrianti Nasrianti; Mulyati Mulyati; Setiawati Setiawati; Mira Asmirajanti; Gunawan Irianto (Jurnal Keperawatan Silampari, 2022)
This study explores the handover implementation of SBAR communication in the 2000 service in the Surgery Room of the Y Regional General Hospital, Papua Province. The research design uses an exploratory phenomenological approach with a purposive approach. The results of this study obtained five themes: nurses' knowledge, understanding, constraints, the benefits of SBAR communication, and nurses' experiences. After researching changes in doing handovers using SBAR communication, namely, the implementation of handovers can be done in a short time, decreasing the number of unexpected events, there is a new Standard Operating Procedure (SOP) based on the theory used. Before the research, the random incidence rate was 60.2%; after the study, the Unexpected Events (KTD) rate was 55.13%. Handover implementation time before the research was obtained with a duration of 25 minutes; then, after it was done, it became 19 minutes. In conclusion, five themes were found, namely nurses' knowledge, nurses' understanding, nurses' constraints, benefits of SBAR communication, and nurses' experiences. Keywords: Handover, SBAR Communication, Nurse